Pengaruh Libur Lebaran Idul Fitri Terhadap Kenaikan Berat Badan Mahasiswa - Hamiati Hamiati; Sitti Nabawi; Najmah Mudiah (Media Literasi Indonesia, 2025)
The Eid al-Fitr holiday is closely associated with changes in eating patterns and decreased physical activity, which can affect body weight. This study aimed to determine the effect of the Eid al-Fitr holiday on changes in body weight among sixth-semester students of the Public Health Study Program at Universitas Muhammadiyah Parepare in 2025. This was a descriptive quantitative study with a cross-sectional approach involving 14 students selected through purposive sampling. Data were collected through direct body weight measurements before and after the holiday using the same digital scale, and an online questionnaire about dietary habits and physical activity. The results showed that 71.43% of students experienced weight gain, 14.29% experienced weight loss, and 14.29% showed no change, with an average weight gain of 0.64 kg. Most students reported increased meal frequency (80%), high-fat food consumption (80%), and decreased physical activity (85%). In conclusion, the Eid holiday influenced weight gain among students due to changes in eating patterns and reduced physical activity. Continuous education on maintaining balanced nutrition and physical activity during holidays is necessary to prevent long-term health risks.